SPATIO-TEMPORAL ANALYSIS OF WESTERN DISTURBANCES OVER PAKISTAN - Ahmad, I.; Sadiq, N. (The Nucleus, 2012)
Considering the vital and unequivocal seasonal importance of western disturbance, it has been analyzed for the period 1973-2007. This study is appropriate to be based on annual, monthly, regional and seasonal investigation for the mentioned period. It is found that the total annual events and days (occurred during the events) are revaluing. The said intervals are also found apprising for the northern and northern plus central parts while considering the whole country, minifying trend is found. Maximum events & days occurred in summer whilst minimum during winter in the monthly analysis. However, the total monthly days and events for different regions show peculiar relations with each other. Seasonal study reveals increasing days and events for all seasons and the highest increase is found in Monsoon season. Further annual and monthly events and days are studied separately for each month through dot plots to observe the shifting pattern of western disturbances for every month. The study is represented through trend models, box plots, dot plots, time series and bar graphs.